Extracellular matrix in the trabecular meshwork: Intraocular pressure regulation and dysregulation in glaucoma. (April 2015) - Vranka, Janice A.; Kelley, Mary J.; Acott, Ted S.; Keller, Kate E.
Abstract: The trabecular meshwork (TM) is located in the anterior segment of the eye and is responsible for regulating the outflow of aqueous humor. Increased resistance to aqueous outflow causes intraocular pressure to increase, which is the primary risk factor for glaucoma. TM cells reside on a series of fenestrated beams and sheets through which the aqueous humor flows to exit the anterior chamber via Schlemm's canal. The outer trabecular cells are phagocytic and are thought to function as a pre-filter. However, most of the outflow resistance is thought to be from the extracellular matrix (ECM) of the juxtacanalicular region, the deepest portion of the TM, and from the inner wall basement membrane of Schlemm's canal. It is becoming increasingly evident that the extracellular milieu is important in maintaining the integrity of the TM. In glaucoma, not only have ultrastructural changes been observed in the ECM of the TM, and a significant number of mutations in ECM genes been noted, but the stiffness of glaucomatous TM appears to be greater than that of normal tissue. Additionally, TGFβ2 has been found to be elevated in the aqueous humor of glaucoma patients and is assumed to be involved in ECM changes deep with the juxtacanalicular region of the TM. This review summarizes the current literature on trabecular ECM as well as the development and function of the TM. Animal models and organ culture models targeting specific ECM molecules to investigate the mechanisms of glaucoma are described. Finally, the growing number of mutations that have been identified in ECM genes and genes that modulate ECM in humans with glaucoma are documented. Highlights: Development and function of the trabecular meshwork are described in detail. Involvement of TGFβ and the extracellular matrix in glaucoma are discussed. Extracellular matrix changes with glaucoma, including compliance of the trabecular meshwork. Mutations in extracellular matrix genes associated with glaucoma in humans are detailed here. Organ culture and animal models used to study intraocular pressure and extracellular matrix are discussed.